2014
DOI: 10.1002/hc.21156
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Types of Ferrocene Dimers Bridged by a Fused Oligothiophene Spacer and Study of Their Electrochemical Oxidation Process via a Mixed‐Valence State

Abstract: We describe the synthesis and electrochemical oxidation properties of ferrocene dimers bridged by a fused oligothiophene spacer (thienothiophene, benzodithiophene, and dithienothiophene), which are designed as new types of ferrocene dimers for the study of the oxidation process via a mixed‐valence state. The electrochemical properties of all ferrocene dimers were examined by a cyclic voltammetry technique. The voltammograms showed a reversible two‐electron oxidation wave derived from the two ferrocene fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…This prevalence stems from their well-defined structure, high chemical stability, together with outstanding electronic properties. Mixed-valence systems containing monomeric thiophene, 2,5-divinylthiophene, or 2,5-diethynylthiophene, received considerable attention with ferrocene, M­(dppe)­Cp*, or M­(dppe)­Cp (M = Ru or Fe) as the capping units. Recently, the mixed valence systems were used to quantitatively discuss the distance dependence of charge-transfer processes with oligomers of various lengths.…”
Section: Introductionmentioning
confidence: 99%
“…This prevalence stems from their well-defined structure, high chemical stability, together with outstanding electronic properties. Mixed-valence systems containing monomeric thiophene, 2,5-divinylthiophene, or 2,5-diethynylthiophene, received considerable attention with ferrocene, M­(dppe)­Cp*, or M­(dppe)­Cp (M = Ru or Fe) as the capping units. Recently, the mixed valence systems were used to quantitatively discuss the distance dependence of charge-transfer processes with oligomers of various lengths.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of bimetallic BDT are rather rare . The bis­(ferrocenyl) derivative, 2,6-bis­(ferrocenyl)­benzo­[1,2- b :4,5- b ″]­dithiophene ( 1 ), was previously synthesized by Negishi ferrocenylation of the appropriate bromo-substituted derivative of BDT .…”
Section: Introductionmentioning
confidence: 99%
“…Actually, the formation of mixed-valence species is often accountable for the aforementioned performances. The factors affecting the formation, stability, and nature of mixed-valence states in multi­(ferrocenyl) derivatives were methodically examined. ,, In particular, it was found that the electron transfer mechanism in mixed-valence intermediates is mostly based on the Marcus–Hush theory …”
Section: Introductionmentioning
confidence: 99%
“…The multi‐step oxidation process derived from the multi‐ferrocene system can be controlled by the π‐conjugated spacer connecting ferrocene fragments due to the fact that the strength of the electronic communication between the mixed‐valent metal centers strongly depends on the electronic nature and length of the linking π‐conjugated spacer. Thus, there have been investigations of multi‐ferrocene derivatives bridged by a wide variety of π‐conjugated spacers such as aromatics (eg, benzene), heteroaromatics (eg, pyrrole, phosphole, furan, thiophene), and their oligomers (eg, oligopyrrole:, oligofuran, oligothiophene).…”
Section: Introductionmentioning
confidence: 99%